Evaluación macroscópica del uso tópico de crema a base de aceite de oliva extra virgen ozonificada en el cierre primario de heridas post-orquiectomía mediante seguimiento de casos en la clínica veterinaria UDLA Quito-Ecuador - Flores Mosquera, Sebastián Francisco (2018)
Ozone is a natural chemical element. Ozone has demonstrated its beneficious aspects in many medical areas. In Ecuador, there are few studies of ozone therapy in Veterinary. This ozone therapy has also been used in superficial wounds; however, there is still much to investigate. In ozone therapy we have to take into account that its healing quality depends on the doses used, its concentration and application method. The medical ozone is an element that has various presentations, but for this investigation a cream was used based on ozone. In this product the ozone concentration is at 4 percent to avoid any harmful effect referring to tissue cellular destruction. To evaluate some benefits of the ozone for the study it was used in post- rchiectomy surgical wound to apply the cream. The main characteristic that will be evaluated in this study will be: the rapid tissue regeneration. In total, 30 canine patients were evaluated at the Universidad de la Americas Veterinarian Clinic after their pre-scrotal orchiectomy was done. After the surgery three obligatory revisions were planned for the patients to control their cicatrization evolution. During these revisions, a table of wound evaluation for a continuous monitoring of the healing process was used. For the study, the patients were divided into two groups of 15 each; through which in one of them the ozone cream was used. As a result, a better macroscopically primary cicatrization was observed in the experimentation group and also a reduction of 26,6 percent of inflammation. At the same time, the statistic study determined a decreased cicatrization time of 33,3 percent between the experimentation group and the operational group. These results inferred that the post-surgery treatment of the experimentation group is more efficient.